ENDOTHELIO- AND CARDIOPROTECTIVE EFFECTS OF VITAMIN В6 AND FOLIC ACID IN MODELLING METHIONINE-INDUCED HYPERHOMOCYSTEINEMIA - Vladimir Provotorov; Mikhail Korokin; Mikhail Pokrovskii; Sergej Povetkin; Galina Lazareva; Aleksandr Stepchenko; Natalya Bystrova (Belgorod National Research University, 2016)
The endotelio- and cardioprotective effects of vitamin B6 (2 mg/kg) and folic acid (0.2 mg/kg) upon modeling of methionine-induced hyperhomocysteinemia via methionine intragastric administration at a dose of 3 g/kg were studied. It was shown that the combined use of vitamin B6 and folic acid allows on the background of a significant reduction in homocysteine concentrations normalizing the endothelial dysfunction coefficient and the parameters of maximum left ventricular pressure in response to intravenous administration of adrenaline. The research was partially supported by the grant of the President of the Russian Federation №MD-4711.2015.7.